Effect of malted-rice amazake on intestinal environment - 井上, 里加子; 入江, 康至; 小川, 亜紀; 吉村, 征浩 (日本薬理学会年会要旨集, 2019)
There are two types of amazake: malted-rice amazake and Sake lees amazake. It has been reported that Sake lees amazake improves human intestinal flora and relieves constipation. But there is no report on malted-rice amazake for improving constipation. The purpose of this study is to conduct a long-term ingestion test on humans and consider whether intake of malted-rice amazake will improve constipation. The subject is adult females with periodic menstrual cycles. Feces were collected in the follicular phase to minimize the influence of premenstrual syndrome. The DNA extracts from feces were analyzed using quantitative PCR using specific primers. The defecation status was investigated by self-report questionnaire.In the defecation state, soft stool of the stool was found significantly by intake of malted-rice amazake in hard stool group. Symptoms of constipation improved in 83% of constipation group. Analysis of intestinal bacterial flora showed a significant decrease the ratio of Firmiscutes / Bacteroidetes in constipation group due to intake of malted-rice amazake. It was suggested that intake of malted-rice amazake changed the construction of gut microbiota as well as the intestinal environment, resulting in improvement in constipation.